A Comparison of Dressing Techniques for Presurgical Closure of Myelomeningocele in the Neonate. Issue 5 (October 2019) - Cartwright, Cathy C.; Igbaseimokumo, Usiakimi; Olsen, Steven
Abstract : ABSTRACT: BACKGROUND: Myelomeningoceles are routinely closed surgically within 24 to 48 hours after birth; the defect and exposed placode must be protected from further damage from excoriation and contamination until surgery. PURPOSE: Two methods to keep the defect moist and clean are used at our large Midwestern children's hospital: the occlusive and the drip. There was no agreement between the neonatal and neurosurgical teams as to which technique was superior, hence the need for a formal evaluation. METHODS: A prospective, randomized trial was conducted to compare the ease of nursing care, cost of supplies, neonatal temperature, and moisture of the placode at the time of closure in neonates with a myelomeningocele. RESULTS: Nurses categorized the occlusive group as easy care (100%) compared with 60% for the drip group, although the difference was not statistically significant ( P = .18). The mean temperatures of the 2 groups before surgery were identical (36.9°C) in both groups. The cost of the drip was 6 times higher than that of the occlusive technique. The placode was assessed as moist in all 13 cases (100%). CONCLUSION: The occlusive technique was easier to care for by all the nurses and was 6 times more cost effective. Both methods kept the placode moist and did not affect the temperature of the baby. Abstract : Supplemental digital content is available in the text.